Synchronous energy extraction from oversized cavities designed with smooth transitions; The 7th International Forum on Strategic Technology (IFOST-2012), September 18-21, 2012, Tomsk - Novikov S. A. Sergey Avtonomovich; Avgustinovich V. A. Vladimir Andreevich; Artemenko S. N. Sergey Nikolaevich; Kaminsky V. L. Valery Ludvigovich; Yushkov Y. G. Yuri Georgievich (2012, 2012)
Title screen